El reúso de dispositivos médicos de un solo uso en una Institución Prestadora de Servicios de Salud (IPS) con un sistema de gestión de la calidad certificado en ISO 9001:2008 (2015)
In Colombia it has been detected that the reuse of many Only One Use Medical Devices (OUMD) in the Health Services Provider (HSP) is done without taking care of the producers warning for not doing it and ignoring the risk for the patient although the only recipient of financial profit is the HSP.